2004
DOI: 10.1002/cncr.20139
|View full text |Cite
|
Sign up to set email alerts
|

Breast carcinoma diagnosis, treatment, and prognosis before and after the introduction of mass mammographic screening

Abstract: BACKGROUND The introduction of breast carcinoma screening leads to early detection and is believed to reduce mortality and increase the proportion of patients for whom breast‐conserving surgery is possible. METHODS In 1992, a population‐based mammographic screening program was introduced in the Dutch city of Tilburg and its surroundings; the program achieved total coverage in 1996. The authors examined the effects of this screening program by investigating disease stage, treatment, and survival among women dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 33 publications
(32 reference statements)
4
22
0
Order By: Relevance
“…We paid special attention to finding all the women who got a breast cancer diagnosis within 2 years after a negative screening examination. The proportion of interval cancers (31% of the cancers in the group that participated screening) in the present work is at the same level as in many previous works (Peeters et al, 1989;Everington et al, 1999;Ernst et al, 2004). This indicates that the quality of the present screening programme is at an acceptable level.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We paid special attention to finding all the women who got a breast cancer diagnosis within 2 years after a negative screening examination. The proportion of interval cancers (31% of the cancers in the group that participated screening) in the present work is at the same level as in many previous works (Peeters et al, 1989;Everington et al, 1999;Ernst et al, 2004). This indicates that the quality of the present screening programme is at an acceptable level.…”
Section: Discussionsupporting
confidence: 79%
“…Recent evaluations have shown that service screening may be even more effective than screening in population-based trials Paci et al, 2002;Gorini et al, 2004). Information of actual participation to screening, data of incident cancers and detailed information of tumour characteristics have provided more precise information of breast cancer prognosis in the screened and not-screened patients (Ernst et al, 2004). Comparison of incident-based breast cancer mortality before and after beginning of screening has shown a significant mortality reduction (Tabar et al, 2003;Gorini et al, 2004).…”
mentioning
confidence: 99%
“…Of these, about half are early-stage, lymph node-negative, hormone receptor-positive tumors. More public health campaigns for regular mammographic screening have increased detection of tumors in early stages, before regional or distant metastasis has occurred [2]. Although adjuvant clinical trials have clearly demonstrated that adjuvant chemotherapy prolongs survival for patients with early-stage breast cancer [3], retrospective analyses of some of these trials suggest that the benefit may be restricted to a subset of patients with either poor or negative expression of estrogen receptor (ER) [4] or patients with human epidermal growth factor receptor (HER)-2 ϩ breast cancer [5].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 3–10% of all BrC patients have metastatic disease at their initial diagnosis; recurrent disease or metastasis occurs in approximately 30% of patients during follow-up after initial treatment [23-26]. The distant metastatic pattern of ILC differs significantly from that of IDC, as it tends to occur as a diffuse thickening of mucosa rather than a discrete nodule.…”
Section: Histotype Route and Patternmentioning
confidence: 99%